(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
Приводятся результаты исследования содержания тяжелых металлов (Ti, Mn, Cr, Fe, Ni, Cu, Zn, Pb, Sr) в растительных (Artemisia austriaca Jacq., Agropyron pectinatum (Bieb.) Beauv. и Potentilla bifurca L.) и почвенных пробах, отобранных в зоне влияния промышленных предприятий г. Павлодара и г. Аксу. The article рrovides results of research on the level of heavy metals such as Ti, Mn, Cr, Fe, Ni, Cu, Zn, Pb, Sr in the soil and vegetable (Artemisia austriaca Jacq., Agropyron pectinatum (Bieb.) Beauv. and Potentilla bifurca L.) samples taken on affected zone of industrial plant of Pavlodar city and Aksu city. DOI: http://dx.doi.org/10.5564/mjas.v10i1.307